Aboriginal use and management of fisheries in British Columbia - Kyle, Rosanne Marie (Allard Research Commons, 2009)
Both the use of and jurisdiction over fisheries resources is an important issue for many First Nations in British Columbia. Historically, fish played an important spiritual, social and economic role in numerous Aboriginal societies. These societies had various methods of managing the resource and, although they had the technological capacity to over-exploit the fisheries, they were able to maintain sustainable levels of fish. Following contact with European settlers, Aboriginal fishers were initially able to continue their traditional methods of fishing as well as expand their use of the fisheries through trade with non- Aboriginals. However, with the opening of the canneries on the coast the fisheries grew in economic importance to non-Aboriginal fishers and management of the resource was gradually but systematically taken over by the state, with various ideologies being used to justify the take-over. Aboriginal fishers lost not only their control over management of the resource, but also their ability to use it as extensively as they once had. Over the years, Aboriginal participation in both the food and commercial fisheries has declined although various government-sponsored programs have been initiated to attempt, with only partial success, to remedy this problem. In the meantime, the Department of Fisheries and Oceans has been battling other problems in the commercial fisheries, including over-capitalization of the fleet and depletion of fish stocks. Management of salmon in particular, because it is an anadromous species which travels through several different jurisdictions, has become extremely complex. It is in this context that much litigation over Aboriginal fishing has been launched. Only a few of the issues have been clarified by the judgments which have resulted and certain myths and ideologies have surfaced repeatedly in many of the decisions. It is likely that the recent decisions of the Supreme Court of Canada on Aboriginal commercial and management rights will result in increased complexity and political controversy. However, problems of fisheries management, including the accommodation of Aboriginal interests, is not unique to British Columbia or even Canada. Similar problems have been experienced elsewhere in the world and various types of co-management regimes have been established in various jurisdictions in an attempt to deal with some of these issues and to recognize a greater role for Aboriginal fishers and communities in fisheries management. It is not clear whether, and to what extent, comanagement will be adopted in British Columbia, or what the role of Aboriginal fishers might be in such a regime. Even if co-management is established, it is highly probable that the state's underlying regulatory regime will remain intact. However, co-management may result in increased Aboriginal participation in both the use and management of the resource.